The Influence of Changes in the Merdeka Curriculum Material and Interactive Learning Amid COVID-19 on Students' Excellency Achievement and Character - Ambarita, Lasmah (Indonesian Journal of Advanced Research, 2025)
This study examines the impact of changes in the Merdeka Curriculum material and interactive learning during the COVID-19 pandemic on students' excellence achievement and character. The objective is to explore how these educational shifts contribute to enhancing students' academic performance and personal development. The research was conducted through surveys and data analysis, focusing on students' responses and performance in interactive learning environments. The study was carried out over six months, with the data collected from 95 students. The results show a positive influence of the Merdeka Curriculum and interactive learning on students' achievements and character development, suggesting that these approaches foster greater academic success and personal growth. This research offers implications for improving future educational practices.